STRUCTURAL STUDY OF MICROPOROUS POLYPROPYLENE HOLLOW-FIBER MEMBRANES MADE BY THE MELT-SPINNING AND COLD-STRETCHING METHOD - KIM, JJ; JANG, TS; KWON, YD; KIM, UY; KIM, SS (ELSEVIER SCIENCE BV, 1994)
Microporous polypropylene hollow fiber membranes were prepared by the melt-spinning and cold-stretching method. Factors affecting the membrane structure were melt-draw ratio, spinning temperature, and annealing temperature. The degree of molecular orientation was affected by the melt-draw ratio and spinning temperature, and the crystallinity of the hollow fiber depended on the melt-draw ratio and annealing temperature. Quantitative analyses of microporous membrane structure were performed by image analysis, bubble point pressure measurement, and mercury porosimetry. The porosity at the surface is smaller than that of the whole membrane. Wetting of the medium and shading in the image brought about the differences in pore size determination by each method.